High frequency of microsatellite instability and its substantial co-existence with KRAS and BRAF mutations in Vietnamese patients with colorectal cancer - Nguyen, Ha Thi (Oncol Lett, 2021)
Tumor heterogeneity and resistance to chemotherapy have been recognized as two major obstacles in the diagnosis and treatment of colorectal cancer (CRC). Microsatellite instability (MSI) and KRAS and BRAF mutations are common diagnostic factors that have been widely used to classify CRC for therapeutics. In the present study, 151 patients with CRC were analyzed from the two most populous ethnic groups of Vietnam, Kinh and Muong, for their MSI status, frequency of KRAS and BRAF mutations, and their clinical implications. MSI-high (MSI-H) was detected in 45.0% (68/151), while mutated KRAS and BRAF were identified in 37.1% (56/151) and 2.6% (4/151) of the cases, respectively. There was a substantial co-existence of MSI-H with KRAS (27/56; 48.2%) and BRAF (3/4; 75.0%) mutations. Statistical analysis showed that MSI-H tumors were significantly associated with colon location (P=0.011) and more advanced T stages (P=0.016). KRAS exon 2 mutations were significantly more likely to be detected in patients who belonged to the Muong ethnic group (P=0.013) or those with no/fewer lymph node metastasis (P=0.048) as compared with their counterparts. In summary, the data revealed typical molecular features of Vietnamese patients with CRC, including a strikingly high rate of MSI-H and its high co-existence with KRAS and BRAF mutations, which should be carefully considered in the future therapeutics for this type of cancer.